The Shape of Anglican Theology : Faith Seeking Wisdom - MacDougall, Scott, (Brill Research Perspectives in Humanities and Social Sciences., 2022)
There are numerous books that offer an historical account of Anglican theology or that detail the lives and work of particular Anglican theologians. Books that focus on the nature and character of Anglican theology itself, however, are hard to find. This volume fills that gap. In The Shape of Anglican Theology, Scott MacDougall examines what it is that makes Anglican theology Anglican. Beginning with a treatment of the ways in which Anglican theology is and is not distinct from other types of Christian theology, he describes the theological features that mark the general boundaries of Anglican theologizing before turning to consider a set of eight interconnected characteristics that provide Anglican theology with its distinctive profile. MacDougall argues that, by setting its boundaries as widely as possible and requiring subscription to specific theological propositions as little as possible, Anglican theology is in essence a wisdom theology that seeks to build the capacity for faithful Christian discernment in belief and practice.